C/EBPβ-LIP mediated activation of the malate-aspartate shuttle sensitizes cells to glycolysis inhibition - Tobias Ackermann; Hidde R. Zuidhof; Christine Müller; Gertrud Kortman; Martijn G.S. Rutten; Mathilde J.C. Broekhuis; Mohamad Amr Zaini; Götz Hartleben; Cornelis F. Calkhoven (Elsevier, 2023)
Objective: Cancer cells use glycolysis for generation of metabolic intermediates and ATP needed for cell growth and proliferation. The transcription factor C/EBPβ-LIP stimulates glycolysis and mitochondrial respiration in cancer cells. We initially observed that high expression of C/EBPβ-LIP makes cells vulnerable to treatment with the glycolysis inhibitor 2-deoxyglucose. The aim of the study was to uncover the involved mechanisms of C/EBPβ-LIP induced sensitivity to glycolysis inhibition. Methods: We used genetically engineered cell lines to examine the effect of C/EBPβ-LIP and -LAP protein isoforms on glycolysis and NADH/NAD+ metabolism in mouse embryonic fibroblasts (MEFs), and triple negative breast cancer (TNBC) cells that endogenously express high levels of C/EBPβ-LIP. Analyses included assays of cell proliferation, cell survival and metabolic flux (OCR and ECAR by Seahorse XF96). Small molecule inhibitors were used to identify underlying metabolic pathways that mediate sensitivity to glycolysis inhibition induced by C/EBPβ-LIP. Results: The transcription factor C/EBPβ-LIP stimulates both glycolysis and the malate-aspartate shuttle (MAS) and increases the sensitivity to glycolysis inhibition (2-deoxyglucose) in fibroblasts and breast cancer cells. Inhibition of glycolysis with ongoing C/EBPβ-LIP-induced MAS activity results in NADH depletion and apoptosis that can be rescued by inhibiting either the MAS or other NAD+-regenerating processes. Conclusion: This study indicates that a low NADH/NAD+ ratio is an essential mediator of 2-deoxyglucose toxicity in cells with high cytoplasmic NAD+-regeneration capacity and that simultaneous inhibition of glycolysis and lowering of the NADH/NAD+ ratio may be considered to treat cancer.